7x-9-11-x=12

Simple and best practice solution for 7x-9-11-x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-9-11-x=12 equation:


Simplifying
7x + -9 + -11 + -1x = 12

Reorder the terms:
-9 + -11 + 7x + -1x = 12

Combine like terms: -9 + -11 = -20
-20 + 7x + -1x = 12

Combine like terms: 7x + -1x = 6x
-20 + 6x = 12

Solving
-20 + 6x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + 6x = 12 + 20

Combine like terms: -20 + 20 = 0
0 + 6x = 12 + 20
6x = 12 + 20

Combine like terms: 12 + 20 = 32
6x = 32

Divide each side by '6'.
x = 5.333333333

Simplifying
x = 5.333333333

See similar equations:

| 8(1-x)-3(2-2x)=2(x+1) | | 5y+27+4y=9 | | 57-5x=4x+23 | | 4x(x-7)+13=27 | | 8-7x=31-4x | | 8.7=d+8.7 | | 5x-(2x+3)=4x-30 | | 4(7x+7)-5=28x+23 | | y=11x^2-90x-68 | | 15x+6y=0 | | (16+2x)*(16+2x)=228 | | 4x-8=4(x+4) | | 4(w+2x)+9w= | | 1.5=r+4.5 | | 1.5=r | | 2x-2y=11 | | 9(3x-5)=(5x+3)+7 | | 5x+1=8x+6 | | -18=162 | | -4(3a+2)=52 | | 48400=(2x+2)(x) | | y=25x^2+10x-24 | | 8.4+b=-22.9 | | -3(x-4)+7x=8x+-8 | | 12+2l+2w=12 | | 4(2a+1)=60 | | 3X+2Y=34 | | 61=4+q | | 7x^2+28x+196=0 | | -5(t-1)+t=5t-9 | | 5x^2+45x+70= | | x*2-6x-4=0 |

Equations solver categories